Genetic divergence among accessions of assai palm based on morphoagronomic descriptors - Oliveira, Maria do Socorro Padilha de; Ferreira, Daniel Furtado; Santos, João Bosco dos (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this research was to estimate the genetic divergence among accessions of the assai palm, sampled in the germplasm collection of Embrapa Amazônia Oriental based on morphoagronomic traits, at Belém, PA. The 22 morphoagronomic traits were evaluated in 87 accessions, from 1995 to 2001. Among the 22 traits, seven were relative to the plant, three to the flowering, three to the fruit, and nine to the fruit production. The traits were analyzed using univariate and multivariate analysis. The estimates of the dissimilarities were obtained by the average Euclidian distance with standardized data, and the groupings by UPGMA and Tocher methods. The accessions presented high variation index in the majority of the characters. Genetic distances among accession pair varied from 0.09 to 1.87, with average of 1.39. The method UPGMA divided the accessions into five groups, while the Tocher method formed 24 groupings. The five accessions indicated as more divergent must be used in breeding programs aiming at the obtention of superior genotypes.